Rapamycin rescues BMP mediated midline craniosynostosis phenotype through reduction of mTOR signaling in a mouse model. Issue 6 (8th August 2018) - Kramer, Kaitrin; Yang, Jingwen; Swanson, W. Benton; Hayano, Satoru; Toda, Masako; Pan, Haichun; Kim, Jin Koo; Krebsbach, Paul H.; Mishina, Yuji
Summary: Craniosynostosis is defined as congenital premature fusion of one or more cranial sutures. While the genetic basis for about 30% of cases is known, the causative genes for the diverse presentations of the remainder of cases are unknown. The recently discovered cranial suture stem cell population affords an opportunity to identify early signaling pathways that contribute to craniosynostosis. We previously demonstrated that enhanced BMP signaling in neural crest cells (caA3 mutants) leads to premature cranial suture fusion resulting in midline craniosynostosis. Since enhanced mTOR signaling in neural crest cells leads to craniofacial bone lesions, we investigated the extent to which mTOR signaling is involved in the pathogenesis of BMP‐mediated craniosynostosis by affecting the suture stem cell population. Our results demonstrate a loss of suture stem cells in the caA3 mutant mice by the newborn stage. We have found increased activation of mTOR signaling in caA3 mutant mice during embryonic stages, but not at the newborn stage. Our study demonstrated that inhibition of mTOR signaling via rapamycin in a time specific manner partially rescued the loss of the suture stem cell population. This study provides insight into how enhanced BMP signaling regulates suture stem cells via mTOR activation.